КУЛЬТУРОЛОГІЧНІ КОНЦЕПТИ ОСВІТОЛОГІЇ ТА РОЗВИТОК ПОЛІКУЛЬТУРНОГО СУСПІЛЬСТВА - Sysoieva, S (Continuing Professional Education: Theory and Practice, 2019)
Such notions as “multicultural education”, “multicultural upbringing”, “intercultural education” in the national scientifi c space and Polish researchers` works are analyzed in the article; the main stages of the development of the culturology as the complex of the humanitarian knowledge about the most common patterns of the culture development are observed; the notion “the culturology of education” is introduced; it is proved that the culturology of education as a part of osvitological knowledge is aimed at the solution of the modern culturological problems in the development of education (multi- and intercultural education, culturological approach in education; the forming of the scientifi c thesaurus of the interdisciplinary researches in the fi eld of osvitologiya at the joint of the “education-culture»).